A Fast Track to Hypoalgesia – The Anaerobic Exercise Effect on Pain Sensitivity - Samuelly-Leichtag, Gil; Kodesh, Einat; Meckel, Yoav; Weissman-Fogel, Irit (International Journal of Sports Medicine, 2018)
Maximal anaerobic exercise, is a short high intensity effort, involves activation of the hypothalamus-pituitary-adrenal axis, and may suggest hypoalgesic effects. In addition, this exercise-induced muscle pain may contribute to hypoalgesia via the pain inhibits pain phenomenon, which is related to the diffuse noxious inhibitory control (DNIC) mechanism. We aimed to investigate whether: 1) a single bout of 30 s maximal anaerobic exercise has an analgesic effect on experimental pain sensitivity; 2) DNIC is the underlying mechanism of anaerobic exercise-induced hypoalgesia (EIH). Fifty healthy subjects participated. The experimental group performed the ‘Wingate Anaerobic Test’ (WAT) and controls set on the bikes without exercising. Psychophysical tests, performed before and after the intervention, in local and remote areas, included: heat (HPT) and pressure pain thresholds (PPT); suprathreshold heat and cold pain stimulation; the conditioned pain modulation (CPM) paradigm testing the DNIC mechanism. Following WAT, PPT and HPT increased (p<0.001) , pain ratings in response to heat and cold stimuli (p<0.001) and CPM (p=0.029) decreased compared with controls. No correlation was found between muscle pain, blood lactate level and EIH. To conclude WAT induces local and remote analgesic effects. The involvement of central pain modulatory processes with DNIC probably not the underline mechanism of EIH.
Keywords: quantitative sensory testing; anaerobic exercise; stress; anxiety; maximal anaerobic performance